Implementasi Model Pembelajaran Discovery Learning untuk Meningkatkan Aktivitas dan Hasil Belajar Matematika Siswa SD - Karjiyati, Victoria (Jurnal PGSD, 2020)
This research aims to improve the activities and results of learning mathematics using the discovery learning model. This type of research is a classroom action research conducted in two cycles. Subjects of this study was grade III B SDIT Generasi Rabbani Bengukulu. The data collection instrument used student activity observation sheets and learning outcomes tests. The data analysis technique uses arithmetic mean and the percentage of learning completeness. The results showed: 1) Teacher activity in the first cycle obtained an average of 3.38 and in the second cycle an average of 3.81, 2) Student activity in the first cycle obtained an average of 3.13 and in the second cycle an average of 3.67, 3) Learning result in the first cycle were obtained an average of 71.43 with learning completeness 64.29 %, an increase in the second cycle obtained an average value of 76.79 with 82.14% completeness learning. The conclusion of this study that the use of the discovery learning model can increase the activity and learning result of class III B students of SDIT Generasi Rabbani, Bengkulu City.